Resumption of Elective Orthopaedic Surgery in the US Epicenter of COVID-19: Overcoming the Continuous Challenges - Krauss, Eugene S.; Cronin, MaryAnne; Dengler, Nancy; Schulman, Debra; Marzano, Marie; Segal, Ayal (Frontiers in Surgery, 2022)
On March 1, 2020, New York State confirmed its first case of COVID-19. An explosive progression of hospitalizations ensued, and all elective surgeries were cancelled between March 23 and May 13, 2020 per federal and state mandate. Upon return to elective surgery in May, 2020, the hospital found itself navigating uncharted territory. The unpredictability of the post-pandemic environment has required the healthcare team to constantly reassess and revise processes to ensure optimal patient outcomes, as well as safe practices for staff providing perioperative care. Health care professionals must continue to remain adaptable and amenable to constant change.